Genome-Wide Analysis of Multidrug and Toxic Compound Extruction Transporters in Grape - Watanabe, Megumi; Otagaki, Shungo; Matsumoto, Shogo; Shiratake, Katsuhiro (Frontiers in Plant Science, 2022)
Grape (Vitis vinifera L.) is an important fruit crop in the world. It is used as a table grape and is also used for raisin and wine production. Grape berries accumulate secondary metabolites, such as anthocyanins, tannins, and resveratrol, which are known as functional compounds for human health. Multidrug and toxic compound extrusion transporter (MATEs) transport secondary metabolites. MATEs also transport other solutes, including organic acids, and toxic xenobiotics, depending on H+ gradients and play various roles in plants. MATE comprises 300–500 amino acid residues and possesses a MATE domain and 8–12 transmembrane domains. In the present study, 59 MATE genes were identified in the grape genome, and phylogenetic analysis revealed the presence of four groups of grape MATEs (Group 1–4). Their information, such as gene structures, protein motifs, predicted subcellular localisations, and gene IDs of four genome annotations, that is, CRIBI v1, CRIBI v2, Genoscope, and Vcost v3, were annotated. The transport substrates and physiological functions of grape MATEs were estimated based on their homology with the analysed MATEs in other plant species. Group 1 may transport toxic compounds and alkaloids, Group 2 may transport polyphenolic compounds, Group 3 may transport organic acids, and Group 4 may transport plant hormones related to signal transduction. In addition to the known anthocyanin transporters, VvMATE37 and VvMATE39, a novel anthocyanin transporter, VvMATE38 in Group 2, was suggested as a key transporter for anthocyanin accumulation in grape berry skin. VvMATE46, VvMATE47, and VvMATE49 in Group 3 may contribute to Al3+ detoxification and Fe2+/Fe3+ translocation via organic acid transport. This study provides helpful and fundamental information for grape MATE studies and resolves the confusion of gene IDs in different genome annotations.